Functional heterogeneity of mast cells in cutaneous inflammation: implications for precision medicine - A, Surui; Ulzii, Dugarmaa; Yadamsuren, Enkhtur; Shi, Jihai (Frontiers in Immunology, 2025)
Inflammatory skin diseases, including atopic dermatitis, psoriasis, and chronic spontaneous urticaria, substantially impair patients’ quality of life. Despite therapeutic advances, current treatments often fail to achieve durable remission, underscoring the need for more precise interventions. Mast cells (MCs), traditionally recognized for their roles in IgE-mediated allergic responses, exhibit marked functional heterogeneity that shapes their pathogenic contributions to chronic skin inflammation. Recent single-cell and spatial transcriptomic analyses have identified discrete MC subsets with distinct inflammatory signatures and tissue-specific distributions, highlighting the complexity of their regulation within disease-specific microenvironments. A key mediator of non-IgE-dependent activation is Mas-related G protein–coupled receptor X2 (MRGPRX2), which engages diverse ligands and triggers receptor-biased signaling pathways, thereby promoting pathological neuroimmune interactions. Although MRGPRX2-targeted small molecules and antibodies have shown preclinical potential, major translational challenges remain, including the limitations of existing animal models and the lack of validated biomarkers. This review delineates MC heterogeneity, summarizes recent insights into MRGPRX2-mediated mechanisms, critically appraises current precision-targeted therapeutic strategies, and proposes solutions to overcome translational barriers. It is suggested that integrating advanced humanized models, longitudinal multi-omics profiling, and standardized functional assays may accelerate clinical translation and support the development of MC-targeted precision medicine.